2005
DOI: 10.1007/s10717-005-0092-3
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion Molding of Sorbents Based on Synthesized Zeolite

Abstract: The possibility of producing complex-profile thin-walled sorbents based on synthesized zeolite is investigated. It is proposed to use natural aluminosilicate as binders. Methods have been developed for controlling properties of zeolite-based molding mixtures by introducing a plasticizer or by alkali or acid modifying the binder structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 1 publication
0
12
0
2
Order By: Relevance
“…The optimum water content was ranged from 25 to 30 wt% and was controlled by the depth of immersion of the cone. The method for determining the optimum molding moisture is described in [13,14]. The granules with diameter of 3 ± 0.1 mm were molded from the paste using the piston extruder.…”
Section: Preparation Of Zeolitementioning
confidence: 99%
“…The optimum water content was ranged from 25 to 30 wt% and was controlled by the depth of immersion of the cone. The method for determining the optimum molding moisture is described in [13,14]. The granules with diameter of 3 ± 0.1 mm were molded from the paste using the piston extruder.…”
Section: Preparation Of Zeolitementioning
confidence: 99%
“…The above-mentioned characteristics are controlled by the active component synthesis per se and shaping steps. Not surprising, the main attention of the academic research groups has been focused on the synthesis of active components, as reported for example in some of the previous studies, while significantly less attention has been paid to catalyst forming or scaling-up to an industrial level. …”
Section: Introductionmentioning
confidence: 99%
“…In fact zeta-potential has already been linked to the rheology of catalyst shaping; ,, however, up to now no clear conclusions about an optimal zeta-potential for extrusion have been made. Many studies are devoted to the rheology of ceramics and zeolites, ,,, unfortunately not focusing on the tensile strength and texture characteristics of final materials. There are very few studies , of impact of rheological behavior of molding masses on textural properties of extrudates.…”
Section: Introductionmentioning
confidence: 99%
“…Well-shaped bodies have been produced in the forms of pellets, tablets, monoliths, granules, and spheres [13][14][15][16]. However, to utilize shaped MOFs successfully for industrial applications, they should have sufficient mechanical strength, chemical stability, attrition resistance, maximal bulk density, and minimal wasted space in the storage vessel [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%